Buffering the healthcare gap: the role of Korean medicine in unmet healthcare needs among care recipients - Minjung Park; Dongsu Kim; Lin Ang; Jennifer Hunter (Frontiers in Medicine, 2026)
Background Population aging is increasing reliance on formal and informal care. Studies consistently report care recipients experiencing higher levels of unmet healthcare needs, highlighting persistent barriers. The compensatory role of traditional medicine in addressing these barriers remains underexplored. This study examines the longitudinal association between care receipt and unmet healthcare needs and evaluates whether traditional Korean Medicine (KM) utilization moderates this association. Methods We analyzed five waves (2014–2018) of the Korea Health Panel Survey (KHPS), yielding 66,188 person-year observations from individuals aged 19 and older. A conditional fixed-effects logit model with year fixed effects was employed to control for time-invariant unobserved heterogeneity and common temporal impacts. Unmet healthcare needs and key independent variables (receiving formal or informal care, KM utilization, and their interaction) were binary. Covariates were selected based on the Andersen Behavioral Model of Health Services Use. Estimation relied on within-person variation in unmet healthcare needs (5,165 individuals; 23,956 person-years), and results are reported as odds ratios (ORs) with 95% confidence intervals (CIs). Results Receiving care was significantly associated with higher odds of unmet healthcare needs (OR = 1.28, 95% CI: 1.08–1.52, p = 0.005). KM utilization was not independently associated with unmet healthcare needs (OR = 1.02, 95% CI: 0.93–1.12). The interaction between receiving care and KM utilization was directionally consistent with a buffering association but did not reach statistical significance (OR = 0.90, 95% CI: 0.67–1.20). Conclusions This study provides longitudinal evidence that adults who receive formal or informal care are more likely to report unmet healthcare needs, even within a system with universal healthcare coverage. Among care recipients, KM utilization was associated with a lower point estimate of unmet healthcare needs, in the direction of a buffering role; however, this interaction did not reach statistical significance and should be interpreted as suggestive. These findings highlight the healthcare access barriers faced by care recipients and suggest that the potential role of KM in meeting their complex healthcare needs warrants confirmation in larger samples with more detailed measures of KM utilization. Policymakers may consider strengthening the integration of KM into community-based care models as further evidence accumulates.